Design with shapes grammars and reinforcement learning. - Ruiz-Montiel, Manuela; Boned-Purkiss, Francisco Javier; Gavilanes-Velaz-de-Medrano, Juan; Jiménez-Morales, Eduardo; Mandow-Andaluz, Lorenzo; Pérez-de-la-Cruz-Molina, José Luis (Elsevier, 2013)
Shape grammars are a powerful and appealing formalism for automatic shape generation in computer-based design systems. This paper presents a proposal complementing the generative power of shape grammars with reinforcement learning techniques. We use simple (naive) shape grammars capable of generating a large variety of different designs. In order to generate those designs that comply with given design requirements, the grammar is subject to a process of machine learning using reinforcement learning techniques. Based on this method, we have developed a system for architectural design, aimed at generating two-dimensional layout schemes of single-family housing units. Using relatively simple grammar rules, we learn to generate schemes that satisfy a set of requirements stated in a design guideline. Obtained results are presented and discussed.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/1733
Keywords: Diseño asistido por ordenador; Arquitectura - Estudio y enseñanza superior - Innovaciones tecnológicas; Computational design; Shape grammars; Reinforcement learning; Architecture